2020
DOI: 10.1097/md.0000000000022448
|View full text |Cite
|
Sign up to set email alerts
|

Can case management improve cancer patients quality of life?

Abstract: Background: Cancer patients are associated with a series of long lasting and stressful treatments and experiencing, and case management (CM) has been widely used and developed with the aim to increase the quality of treatments and improve the patient care services. The purpose of this review is to identify and synthesize the evidence of randomized controlled trial studies to prove that case management could be one way to address the quality of life of cancer patients. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…This is a common issue faced the included reviews. Five of the eight reviews failed to conduct meta-analysis due to the heterogeneity [9,11,19,23,24]. Joo and Huber [22] conducted a review of reviews on the effect of CM on health care utilization outcome of chronic illness patients, they recognized the same problem and suggested using valid and standardized tools to minimize the differences in measurements.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is a common issue faced the included reviews. Five of the eight reviews failed to conduct meta-analysis due to the heterogeneity [9,11,19,23,24]. Joo and Huber [22] conducted a review of reviews on the effect of CM on health care utilization outcome of chronic illness patients, they recognized the same problem and suggested using valid and standardized tools to minimize the differences in measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Joo et al [9] found that CM interventions improved QoL of cancer patients. Yin and colleagues [24] revealed that cancer patients achieved better physical and psychological condition through symptom management, needs assessment, direct referrals, and other services in CM. However, summarized results in our review show that the CM had equivocal effect on cancer patients' global QoL and dimensions including psychological, physical, role, emotional and social function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations